2014
DOI: 10.4314/njp.v41i3.17
|View full text |Cite
|
Sign up to set email alerts
|

Conjoined twins in Edo state of Nigeria; a report of the first surviving set

Abstract: Abstract:The term conjoined twins refers to babies who are physically joined at some point. It is a rare condition with an estimated incidence of 1 per 200,000 live births. We report our experience with conjoined twins over a twelve year period in tertiary hospital in Nigeria and a case of the first set of conjoined twin survivors in Benin City, Nigeria. Over the last twelve years (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011), three cases of conjoined twin have been recorded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The incidence of conjoined twins' falls in the range of 1:50,000 to 1:100,000 live births, with 40-60% being stillborn and about 35% of the live births not surviving beyond 24 hours [4]. The exact incidence of conjoint twins in Nigeria is not known as there are instances of under-reporting, largely due to the relatively poor prognosis and stigmatisation associated with conjoined twinning [5]. In Nigeria, the earliest reported case of conjoined twins were born in Sokoto on 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of conjoined twins' falls in the range of 1:50,000 to 1:100,000 live births, with 40-60% being stillborn and about 35% of the live births not surviving beyond 24 hours [4]. The exact incidence of conjoint twins in Nigeria is not known as there are instances of under-reporting, largely due to the relatively poor prognosis and stigmatisation associated with conjoined twinning [5]. In Nigeria, the earliest reported case of conjoined twins were born in Sokoto on 20…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Amuabunos et al in Benin city, Edo State Nigeria reported a case of the first set of conjoined twins survivor managed in University of Benin Teaching Hospital, 3 other sets of non-surviving conjoined twins had been managed in that facility [5]. Amuabunos et al also observed that 18 cases of conjoined twins had been reported in Nigeria over 76 years; from 1935 to 2012, across various health facilities in Nigeria [5]. Conjoined twins are associated with a higher predominance of the female sex [4].…”
Section: Introductionmentioning
confidence: 99%